Distinct combinations of NF-kappa B subunits determine the specificity of transcriptional activation. - Perkins, N D (1992)
The nuclear factor that binds to the kappa light-chain enhancer of B cells (NF-kappa B) is a transcription factor that regulates the expression of a variety of cellular and viral genes. NF-kappa B is composed of distinct subunits, and at least four independent genes (p105, p100, p65, and c-rel) have been isolated that encode related proteins that bind kappa B sites. Because it is possible that specific interactions of different subunits can allow selective gene activation, we have characterized the specificity of transcriptional activation by various combinations of these subunits. When tested alone, an approximately 49-kDa form (p49) of the p100 protein bound weakly to kappa B, but p49 associated with p65 to bind efficiently to this site. Furthermore, p49 acted in combination with either p65 or a Rel/VP16 fusion protein to activate kappa B-dependent transcription in Jurkat T leukemia cells. The p49/p65 or p49/Rel combination stimulated transcription mediated by the canonical kappa B site but did not stimulate reporter genes containing interleukin 2 receptor alpha or major histocompatibility complex kappa B elements, despite its ability to bind to these sites. Transactivation mediated by the p49/p100 and p65 NF-kappa B proteins is therefore sensitive to minor changes in the sequence of the kappa B site. Specificity determined by the association of NF-kappa B subunits provides a mechanism to selectively regulate variant kappa B sites associated with different cellular and viral genes.